2012
DOI: 10.1111/j.1365-2036.2012.05100.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of infliximab and adalimumab in Crohn's disease: a single centre study

Abstract: SUMMARY BackgroundInfliximab and adalimumab are highly effective in Crohn's Disease (CD). This is supported by clinical trials and open-label studies using either infliximab or adalimumab, thus not allowing a proper comparison between these anti-TNFs in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 41 publications
4
44
1
1
Order By: Relevance
“…A longitudinal * This work was supported by 973 Project Grants 2010CB833600, 2013CB911103, 2012CB724500, and 2010CB735605; National Natural Sci- study involving 93 Crohn's disease patients was performed to compare the effectiveness of Infliximab and Adalimumab. The study suggested that no obvious differences could be found in obtaining and maintaining remission (8). Another study drew a similar conclusion, claiming that the difference between Infliximab and Adalimumab is not obvious because the long term maintenance of the clinical remission between the two antibodies and their effectiveness are similar in both primary and secondary-tertiary centers (9).…”
Section: Tnf␣-targeting Therapy With the Use Of The Drugs Etanerceptmentioning
confidence: 89%
“…A longitudinal * This work was supported by 973 Project Grants 2010CB833600, 2013CB911103, 2012CB724500, and 2010CB735605; National Natural Sci- study involving 93 Crohn's disease patients was performed to compare the effectiveness of Infliximab and Adalimumab. The study suggested that no obvious differences could be found in obtaining and maintaining remission (8). Another study drew a similar conclusion, claiming that the difference between Infliximab and Adalimumab is not obvious because the long term maintenance of the clinical remission between the two antibodies and their effectiveness are similar in both primary and secondary-tertiary centers (9).…”
Section: Tnf␣-targeting Therapy With the Use Of The Drugs Etanerceptmentioning
confidence: 89%
“…Single centre nonrandomised open-label cohort studies have shown comparable efficacy and safety between IFX and ADA at 1 year. 23 Yet, issues of small study size, the absence of randomisation, and the lack of objective assessments of disease activity preclude firm conclusions on comparative efficacy from these data. Further, one 27 and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) commonly affects women of reproductive age 1 , and is often managed using drugs recognised to have potential for toxicity in adults 2,3 . Since it is unethical to test the safety of almost all drugs in pregnancy in clinical trials, the potential for teratogenicity of drugs taken during pregnancy has been a pressing and natural concern of all pregnant women or those attempting to become so.…”
Section: Introductionmentioning
confidence: 99%